Cambodian refugees in Ontario : resettlement, religion, and identity - McLellan, Janet, 1952- (University of Toronto Press, 2009)
Janet McLellan uses ten years of ethnographic fieldwork, including extensive interviews, to highlight the difficulties Cambodians have faced in Canada.